2020
DOI: 10.3390/eng1020014
|View full text |Cite
|
Sign up to set email alerts
|

Microanalysis of Selected NSAIDs Using the Spectrophotometric Method

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are the group of drugs most commonly used in medicine. They are available over the counter to treat fevers and pains of various origins. The clinical and pharmaceutical analysis of these drugs requires effective analytical procedures for drug quality control, pharmacodynamic and pharmacokinetic studies. This article presents the spectrophotometric method that was used to analyze selected drugs from the NSAID group. The conditions for the determination of selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…TNX obstructs the actions of COX enzymes, the chemicals responsible for pain and inflammation. Various techniques have been employed to determine the levels of TNX, including HPLC 15 , UV 16 , fluorescence 17 , flow injection 18 , and ionpair 19 spectrophotometry, electro analytical 20 , voltammetry 21 , X-ray 22 , scanning electron microscopy (SEM), X-ray diffraction, dynamic light scattering (DLS), Fourier transform infrared (FTIR) 23 , photo catalysis 24 , and immunochromatographic strip with colloidal gold 25 .…”
Section: Introductionmentioning
confidence: 99%
“…TNX obstructs the actions of COX enzymes, the chemicals responsible for pain and inflammation. Various techniques have been employed to determine the levels of TNX, including HPLC 15 , UV 16 , fluorescence 17 , flow injection 18 , and ionpair 19 spectrophotometry, electro analytical 20 , voltammetry 21 , X-ray 22 , scanning electron microscopy (SEM), X-ray diffraction, dynamic light scattering (DLS), Fourier transform infrared (FTIR) 23 , photo catalysis 24 , and immunochromatographic strip with colloidal gold 25 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide choice of various analytical techniques for the assay of meloxicam in pharmaceuticals available in the literature [8][9][10][11][12][13][14][15][16][17][18]. Spectrophotometry is one of the most commonly used methods for the determination of this drug.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important member of the family of 2-aryl propionic acid derivatives; which commonly used for reducing moderate to severe pain, fever, inflammation, and stiffness owing to arthritis, gout, injury (such as fractures), tonsillitis and bursitis. It has also recently been reported that naproxen is *Corresponding Author Institutional Email: Afsharalihosseini@iauctb.ac.ir (A. Alihosseini) effectively used in preventing the progression of bladder cancer [3] Naproxen inhibits COX-1 and COX-2 enzymes can prevent the biosynthesis of prostaglandins [4]. Naproxen (NP) is widely used to treat acute to chronic pain most commonly in veterinary and human medicine because it is available without a prescription.…”
Section: Introductionmentioning
confidence: 99%